Pengaruh Propilen Glikol terhadap Laju Difusi Krim Natrium Diklofenak dengan Basis Hidrofobik Secara Invitro (Journal of Tropical Pharmacy and Chemistry, 2025)
The research on effect of propylene glycol in diffusion of cream diclofenac sodium from hydrophobic base with in-vitro. The research has been used for concentrations propylene glycol (0, 3, 5, and 7%). The stability test included organoleptic, pH, viscosity, consistency, flow type for 56 days of storge, and diffusion test used diffusion franz cell and membrane spangler. The result showed that formula diclofenac sodium cream contained propylene glycol 7% was the one best in diffusion of 0.0203 ppm/menit.